Public management a research overview - Entwistle, Tom 1966- (Routledge, 2022)
Public Management: A Research Overview provides a structured survey of the state of the art of public management research. Looking at the enduring themes of bureaucracy, autonomy, markets and collaboration, each chapter introduces key foundational studies before reviewing contemporary research. Although originally intended to maximise efficiency, work on bureaucracy points to the problems of red tape, contested accountabilities, performance management, merit and public service motivation. Autonomy research asks whether reforms intended to free subservient agencies from red tape and political interference have delivered the goods. Are autonomous service managers more focused on the needs of citizen-consumers and more entrepreneurial in their appetite for innovation? Marketisation reforms take a further step away from bureaucratic forms of control by exposing public services to market forces of one form or another. Competitive contracting and privatisation put public services into real markets while quasi-markets and yardstick competition try to recreate these pressures without private ownership. Perhaps reacting to the fragmentation unleashed by unbundling and marketisation, collaboration promises to deliver improvement through voluntary processes of negotiation and exchange. Vertical forms of collaboration between different levels of government, or between governments and citizens, promise a better match between policies and problems. Lateral collaboration between agencies working at the same level are intended to tackle the so-called wicked issues that fall between jurisdictions or else to share services and unlock economies of scale. The book concludes by considering the new challenges facing public management from global warming to the rise of populism and affective polarisation.